Tagalog stories for language learners folktales and stories in Filipino and English - Barrios, Joi (Tuttle Publishing, 2021)
This book introduces 40 stories from the Phillipines in parallel Tagalog and English versions presented on facing pages. Each story has cultural notes, vocabulary lists, exercises, comprehension questions and online audio recordings by a native speaker as well as an illustration.